2021
DOI: 10.1186/s12884-021-04174-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between adverse pregnancy outcomes and preceding risk factors: a cross-sectional study from Nashik District, India

Abstract: Background The preconception phase of women’s life cycle is critical but comparatively ignored. The presence of health risks is judged as hazardous to the wellbeing of women and their offspring. This study aimed to estimate the prevalence of various pregnancy outcomes and assess the association between certain risk factors and adverse outcomes. Methods As a part of a preconception care intervention project, a baseline survey was conducted in four b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5] Genuine reason for consanguineous marriage in the community is primarily social and cultural. 2,3,6 Several social studies indicated that reasons for consanguinity are: Stability in marriage due to high Compatibility between husband, wife, and between couples and Family. Who shares the same social relationship before the marriage and after the marriage, it is considered favorable for Status of women who will have a better relationship with her in-laws, reduces the possibility of a hidden uncertainty in health and financial issues, strengthens the financial ties and provides solidarity.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5] Genuine reason for consanguineous marriage in the community is primarily social and cultural. 2,3,6 Several social studies indicated that reasons for consanguinity are: Stability in marriage due to high Compatibility between husband, wife, and between couples and Family. Who shares the same social relationship before the marriage and after the marriage, it is considered favorable for Status of women who will have a better relationship with her in-laws, reduces the possibility of a hidden uncertainty in health and financial issues, strengthens the financial ties and provides solidarity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Girl's parents prefer to have their daughter living near them and to enjoy the presence of their grandchildren, and lastly the family wants to keep their wealth or property within the family. [1][2][3]6 Socially, consanguineous marriages may provide strength to relationships, the economic condition in families. 3,5 But many health-care providers and genetic scientists consider consanguineous marriage as the risk to health.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations